1999
DOI: 10.1044/jslhr.4201.206
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Productivity in Children With Normal Language and SLI

Abstract: Children with specific language impairment (SLI) are known to display persistent difficulties with inflectional morphology--in particular, the overuse of unmarked grammatical forms (i.e., zero-marking). Yet, several recent studies have shown that English-speaking children with SLI, like their normal language peers (NL), demonstrate a considerable degree of productive language abilities (e.g., Bishop, 1994; Loeb & Leonard, 1991; Oetting & Horohov, 1997). In this study, we explore productivity in the English pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
231
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(257 citation statements)
references
References 28 publications
22
231
4
Order By: Relevance
“…Thus, adding another syllable to the inflected word is apparently more difficult than having a consonant cluster (see similar findings by Marchman, Wulfeck, & Weismer, 1999).…”
Section: A Phonological Approachsupporting
confidence: 52%
“…Thus, adding another syllable to the inflected word is apparently more difficult than having a consonant cluster (see similar findings by Marchman, Wulfeck, & Weismer, 1999).…”
Section: A Phonological Approachsupporting
confidence: 52%
“…those showing over-regularizations such as throwed) in illustrating that children with SLI possess some degree of knowledge of past tense use in spite of their limited skill in this area (e.g. Eyer & Leonard, 1995;Oetting & Horohov, 1997;Marchman et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Oetting and Horohov (1997), Marchman, Wulfeck, and Ellis Weismer (1999), Norbury, Bishop, and Briscoe (2001), and van der Lely and Ullman (2001) have all reported that children with SLI were more likely to use past tense with frequently occurring verbs than with infrequently occurring verbs. However, other findings have not been uniform across the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Again, some form of contrast, pre-emption or blocking (the term used with a slightly more specific meaning here than in the discussion above) seems to play an important role. A number of studies [23][24][25] have demonstrated a negative correlation across verbs between the rate of overgeneralization error and the relative or absolute frequency of the correct form (e.g., went, threw, slept, and sat).Again, though, pre-emption cannot be the whole story, as it cannot explain performance with novel items, for which no pre-empting past-tense form can be stored in memory. One possibility [26][27][28] is that children set up a rule for regular verbs (e.g., add -ed) and simply memorize the exceptions as a fixed list of stems to which a particular irregular rule applies (e.g.,…”
mentioning
confidence: 97%
“…Again, some form of contrast, pre-emption or blocking (the term used with a slightly more specific meaning here than in the discussion above) seems to play an important role. A number of studies [23][24][25] have demonstrated a negative correlation across verbs between the rate of overgeneralization error and the relative or absolute frequency of the correct form (e.g., went, threw, slept, and sat).…”
Section: Inflectional Morphologymentioning
confidence: 99%